Políticas de formação docente continuada na perspectiva da constituinte escolar : Rio Grande do Sul/1999-2002 - Facenda, Luisa Cadorim (2009)
This work relates the theme of teacher education policy and continuing the Student Constitution of Rio Grande do Sul, action directed to education, triggered by the Secretary of State from 1999 to 2002. I understand that a policy of continuous teacher training is included within the educational policy, which regulates and governs matters relating to education, the organization of the education system to train teachers. This policy is revealed as a process in each historical period. Thus, I introduce the term teacher training continued based on the idea that it has a definite beginning, however, has no end. So consider a policy of continuous teacher training actions planned, developed and implemented by a particular government, aimed to ensure training, information, improvement and advancement of professionals. The central question that permeates this work revolves around issues that show the School Constitution - EC as a policy of continuous teacher training. To answer it, has as main objective to report its genesis and identify aspects that ensured as a public policy of continuous teacher training, by doing so, examine the design of teacher that guided it. To develop the research, I used a qualitative method of documentary analysis. The School Constitution occurred in the post-LDBEN 9394/96, and discusses, among other things, the continuing education. The action of the government of this state was in a decade in which they showed true wealth of proposals and conceptions of teacher education. It signals traces of a government policy that was intended to be of state, derived the idea of continuity beyond the government administration, however, to end the government Olivio Dutra, the EC also came to an end. With the development of research, I understand that the construction of a political and pedagogical project may involve a process of continued teacher training. The organization of such training should take as its starting point the very practice of teaching, making school a "democratic" as an area trainer and empowering educational institution, as it seeks to promote the participation of the school community (students, parents, faculty, staff and management team), attempted to look at the context in which work is performed in teaching, rescue and problematize, to address issues of school routine. I believe the investment in teacher training continued as an essential element for achieving progress in improving the quality of education, so that action can become overriding directive of public policies in education, because one must go beyond specific programs and establish a permanent policy training within the State